Read, Reason, Write - Seyler Dorothy U (Mc Graw Hill Higher Education, 2009)
With this ninth edition, Read, Reason, Write becomes 25 years old and although some important new material strengthens the ninth edition, the essential character of Read, Reason, Write remains the same. This text still unites instruction in critical reading and analysis, argument, and research strategies with a rich collection of readings that provide both practice for these skills and new ideas and insights for readers.